Geographical Distribution And Seasonal Fluctuation Of Snails And Their Intermediate Hosts In The Blue Nile STATE, SUDAN - Ahmed, Dr. Mohamed Khalid Taha (Gezira Journal of Health Sciences, 2018)
The present study was carried out at the Blue Nile State to assess the distribution of snails in freshwater canals especially the intermediate hosts of Schistosoma and their epidemiology. Snails were collected by the standard scooping method, from small water bodies and canals. The snails’ habitats were critically studied. Collected aquatic forms were transferred to the prepared laboratory, where snails were cleaned from the vegetation cover and the attached debris, the snails were then counted and sorted to species and separated in labelled plastic bowls The study recorded the presence of the Prosobrancha (Melanoides.tuberculata, Lanistus.carinatus and Cleopatra. bulimoides) which are of no medical importance and the Pulmonate (Bulinus.truncatus, Bulinus.forskalii and Biomphalaria pfeifferi) of which Bulinus.for skalii is of no medical importance. The dominated snail was Melanoides.tuberculata. The density of all snails dropped during the flood season, except for Melanoides.tuberculata which is able to protect its soft tissues inside the snails by the operculum.  A significant relation (p < 0.05) was found between the physical (turbidity and temperature), chemical and biological (decaying matter) characteristics of the water bodies and reproduction of snails. The density of the snails was negatively affected by distance of the site from the point of water entrance into the canal, season, abundance and density of vegetation. The results showed infectivity of Bulinus.truncatus in water sites frequently visited by the people indicating that schistosomiasis is endemic in the area. The results showed that Bulinus.truncatus is highly susceptible to S. haematobium infection. هذه الدراسة نفذت في ولاية النيل الأزرق لتحديد توزيع الحلزونات في قنوات الماء العذب خصوصاً العائل الوسيط للشستوسوما ووبائيته . أجريت المسوحات الحلزونية لفترة 12 شهر خلال الفترة من مايو 2009 الى أبريل 2010 مستخدمين في ذلك المجرفة. أما بيئة الحلزونات فقد دُرست بشكل بالغ الأهمية فكل الأشكال المائية التي جمعت نقلت الى المعمل المحضر لذلك ، حيث تم نظافة الحلزونات مِنْ غطاءِ النباتاتَ والحطامَ الملحقَ، ثمّ حسابَ وتصنّيفَ الحلزونات إلى النوعِ المحدد وفُصِلَها في طاساتَ بلاستيكيةَ موضح عليها أسماء الحلزونات .وجدت ستة أنواع من الحلزونات في قنوات هذه الولاية هي الحلزونات الرئوية ذات الأهمية الطبية للعائل الوسيط للبلهارسيا التي تصيب الإنسان والتي تنقل بلهارسيا المجاري البولية وبلهارسيا الامعاء على التوالي . Bulinus truncatus (بولاينس ترنكاتس) Biomphalaria pfeifferi, (بيومفالاريا فيفراى) و Bulinus forskalii  (بولاينس فورسكالي) الذي ليس له أهمية طبية . بينما الحلزونات غير الرئوية مثل Melanoides tuberculata,  (ميلانويدز تيوبركيوليتا) كان له السيطرة علي الحلزونات الأخرى و Cleopatra bulimoides (كليوباترا بوليمويدز)  و  Lanistus.carinatus  (لانستس كارينيتس) وهذه ليست ذات أهمية طبية . كثافة كل الحلزونات إنخفضت خلال موسم الفيضان ما عدا Melanoides tuberculata (ميلانويدز تيوبركيوليتا) الذي يحمي الأنسجة الداخلية بغطاء ولا يتأثر بتعكير الماء. هنالك علاقة هامة (p < 0.05) وجدت بين الخصائص الفيزيائية والكيميائية والإحيائية للأجسام المائية وتكاثر أو توالد الحلزونات . كثافة الحلزوناتِ تتأثر سلبياً بمسافةِ الموقعِ مِنْ نقطةِ مدخلِ الماءِ إلى القناةِ والفصلِ من السنة ووفرةِ وكثافةِ النباتاتِ . أثبتت النَتائِجُ قابليةَ اصابة Bulinus truncatus (بولاينس ترنكاتس) في مواقعِ الماءِ التي تزارَ بشكل متكرّر مِن قِبل الناسِ مما يُشيرُ بأنّ مرض البلهارسيا مستوطنُ في المنطقةِ. كما أثبتت النَتائِجُ أيضاً بأن Bulinus truncatus (بولاينس ترنكاتس) إلى حدٍ كبير معرّض للعدوى ببلهارسيا المجاري البولية .